Особливості росту та розвитку генеративних рослин видів роду Symphytum L. у Національному ботанічному саду ім. М.М. Гришка НАН України - Vergun, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The peculiarities of growth generative shoots of Symphytum L. species in M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are showed. The total content of carbohydrates and photosynthesis pigments of leaves in period of active vegetation is determined.